Thomas Aquinas's Prime Matter Pluralism - Peck, John W. (The Thomist, 2025)
Prime Matter Pluralism (PMP) states that while the prime matter of all terrestrial bodies is the same, there is a unique prime matter for each celestial body. Prime matters are distinct in virtue of being in potentiality to different forms. Steven Baldner argues that although Thomas Aquinas endorsed PMP in Summa theologiae I, he ultimately rejected it in his De caelo commentary and De substantiis separatis. Besides exegetical evidence for this claim, Baldner presents a philosophical objection to PMP: according to PMP, distinct prime matters are restricted in their respective potentialities; such restriction requires form, however; therefore, prime matter is not pure potentiality. Since prime matter is pure potentiality, PMP is false. Pace Baldner, I argue that Aquinas endorsed PMP as heartily in the later works as in STh I. Moreover, he resisted substantially the same objection to PMP as Baldner’s several times. In particular, Aquinas repeatedly rejected the claim that the restriction of prime matter’s potentiality requires form. In that case, when Aquinas calls prime matter “pure potentiality,” he means that it is formless of itself, not that it is in potentiality to any form whatsoever.